Composition for forming solar cell electrode and electrode formed therefrom
By using conductive powder, glass frit with specific calculation formulas and organic carrier compositions, the stability problem of solar cells in high temperature, polyhumidity and acidic environments is solved, and a solar cell electrode with high reliability and long-term stability is achieved.
Patent Information
- Application Number
- CN202110608069.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2021-06-01
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-06-01
AI Technical Summary
When existing solar cells are used in high-temperature and humid environments, the increase in electronic resistance leads to a reduction in power and is easily damaged in an acidic environment, affecting long-term stability.
A composition consisting of conductive powder, glass frit of specific calculation formulas and organic carriers is used to form a solar cell electrode. The frit consists of acidic and basic compounds, which ensures that the composition is stable in an acidic environment by calculation of specific mole percentages and acidity.
It improves the reliability and long-term stability of solar cell modules, reduces the risk of electrical characteristics damage in acidic environments, and extends the service life of the battery.
Smart Images

Figure CN114446509B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for forming a solar cell electrode and a solar cell electrode formed using the composition, and more particularly, to a composition for forming a solar cell electrode having high module reliability and excellent long-term stability and a solar cell electrode formed using the composition. Background Art
[0002] Solar cells generate electricity by converting the photon of sunlight into electricity through the photoelectric effect of the pn junction. In a solar cell, a front cell and a rear cell are formed on the upper and lower surfaces of a semiconductor wafer or substrate forming a pn junction, respectively. In a solar cell, the photoelectric effect of the pn junction is caused by sunlight incident on the semiconductor wafer, and the electrons generated thereby provide an electric current that flows to the outside through the electric current. The electrodes of such a solar cell can be formed on the surface of the wafer by applying, patterning and firing the electrode paste composition.
[0003] Since solar cells need to generate electricity for a long time in a variety of external environments, they need to have long-term stability. In particular, when solar cells are exposed to high temperature and high humidity, problems related to electrical properties such as increased resistance of electrons leading to reduced power will occur, which increases the importance of long-term stability of the module.
[0004] Recently, solar cell companies have evaluated the acid resistance of electrodes as an important factor in order to improve the reliability and long-term stability of solar cell modules. When making solar cell modules, EVA film is used in the process of packaging electrodes. When it is set for a long time and generates electricity, it decomposes with water due to UV, thereby generating acetic acid as a byproduct. Acetic acid chemically damages the glass in the electrode, thereby causing the resistance between the emitter and the electrode to increase and reduce efficiency.
[0005] Therefore, there is a need to develop a glass composition for solar cell electrodes that does not react sensitively to chemical changes even when exposed to acid and can maintain electrical properties with guaranteed long-term stability. Summary of the invention
[0006] Problem to be solved
[0007] An object of the present invention is to provide a composition for forming a solar cell electrode having high module reliability and excellent long-term stability.
[0008] Another object of the present invention is to provide a solar cell electrode formed using the composition.
[0009] Solutions to the problem
[0010] 1. According to one embodiment, a composition for forming a solar cell electrode is provided. The composition may include a conductive powder, a glass frit, and an organic carrier, and the glass frit may be calculated by the following formula 1, and α is greater than 0.9.
[0011] <Formula 1>
[0012]
[0013] In formula 1,
[0014] C i is the content of each acidic compound constituting the glass frit (unit: molar percentage),
[0015] A i is the acidity of each of the acidic compounds constituting the glass frit,
[0016] n is the number of acidic compounds that make up the glass frit,
[0017] C j is the content of each alkaline compound constituting the glass frit (unit: mole percentage),
[0018] A j is the acidity of each alkaline compound constituting the glass frit,
[0019] m is the number of kinds of basic compounds constituting the glass frit.
[0020] 2. In the first example, the glass frit may include an acidic compound at 40 mol % to 60 mol %.
[0021] 3. In the first example or the second example, the glass frit may include a basic compound at 1 mol % to 25 mol %.
[0022] 4. In one of the first to third examples, the glass frit may include the acidic compound and the basic compound in a total amount of 45 mol % to 75 mol %.
[0023] 5. In one of the first to fourth examples, the glass frit can be calculated by the formula 1, and α is 0.9 to 5.
[0024] 6. In one of the first to fifth examples, the glass frit may include one or more elements selected from the group consisting of lead (Pb), bismuth (Bi), tellurium (Te), lithium (Li), sodium (Na), phosphorus (P), silicon (Si), zinc (Zn), germanium (Ge), calcium (Ca), gallium (Ga), silver (Ag), iron (Fe), tungsten (W), magnesium (Mg), molybdenum (Mo), niobium (Nb), strontium (Sr), titanium (Ti), tin (Sn), indium (In), vanadium (V), barium (Ba), nickel (Ni), copper (Cu), potassium (K), selenium (Se), arsenic (As), cobalt (Co), zirconium (Zr), manganese (Mn), aluminum (Al), thallium (Tl), tantalum (Ta), cesium (Cs), cerium (Ce), and boron (B).
[0025] 7. In one of the first to sixth examples, the glass frit may contain lead (Pb), bismuth (Bi) and tellurium (Te), and the glass frit may contain lead (Pb) and bismuth (Bi) in a total amount of 20 mol % to 45 mol %, and contain tellurium (Te) in a total amount of 10 mol % to 60 mol %.
[0026] 8. In the seventh example, the glass frit may further include one or more elements selected from the group consisting of lithium (Li), sodium (Na), magnesium (Mg), zinc (Zn), tungsten (W), silicon (Si), and boron (B).
[0027] 9. In the eighth example, the lithium (Li) may be included in an amount of 0.1 to 25 mole percent, the sodium (Na) may be included in an amount of 0.1 to 10 mole percent, the magnesium (Mg) may be included in an amount of 0.1 to 25 mole percent, the zinc (Zn) may be included in an amount of 0.1 to 25 mole percent, the tungsten (W) may be included in an amount of 0.1 to 30 mole percent, the silicon (Si) may be included in an amount of 0.1 to 30 mole percent, and the boron (B) may be included in an amount of 0.1 to 10 mole percent.
[0028] 10. In any one of the first to ninth examples, the composition may further include one or more of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoaming agent, a pigment, a UV stabilizer, an antioxidant, and a coupling agent.
[0029] 11. In one of the first to tenth examples, the composition may include 60 weight percent to 95 weight percent of the conductive powder; 0.1 weight percent to 20 weight percent of the glass frit; and 1 weight percent to 30 weight percent of the organic vehicle.
[0030] 12. According to another embodiment, a solar cell electrode is provided. The electrode may be formed using one of the compositions of the first to eleventh examples.
[0031] Effects of the Invention
[0032] The present invention has the effect of providing a composition for forming a solar cell electrode having high module reliability and excellent long-term stability, and a solar cell electrode formed using the composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The figure briefly shows a solar cell according to an example of the present invention. DETAILED DESCRIPTION
[0034] In this specification, unless otherwise clearly indicated in the wording, the singular expression includes the plural expression.
[0035] In the process of describing the present invention, if it is determined that the detailed description of the related known technology will unnecessarily obscure the gist of the present invention, the detailed description thereof will be omitted.
[0036] The terms “include / comprise” or “have” in this specification are intended to specify the presence of features or structural elements recorded in the specification, rather than excluding the possibility of adding one or more other features or structural elements in advance.
[0037] In the process of interpreting structural elements, even if there is no explicit record of it, it should be interpreted as including the error range.
[0038] In the present specification, “to” in “a to b” expressing a numerical range is defined as ≥a and ≤b.
[0039] In this specification, unless otherwise indicated, the content of each component of the glass frit is based on the total molar number of the glass frit and is converted based on the oxide.
[0040] Composition for forming solar cell electrodes
[0041] The composition for forming a solar cell electrode according to one embodiment of the present invention may include conductive powder, glass frit, and an organic vehicle, and the glass frit is calculated by the following formula 1, and α is greater than 0.9.
[0042] Hereinafter, each component of the composition for forming a solar cell electrode will be described in further detail.
[0043] Conductive powder
[0044] The conductive powder may include one or more metal powders such as silver (Ag), gold (Au), platinum (Pt), palladium (Pd), aluminum (Al) and nickel (Ni), but is not limited thereto. According to one example, the conductive powder may include silver powder.
[0045] The particle shape of the conductive powder is not particularly limited, and various shapes such as spherical, plate-like, or amorphous particles can be used.
[0046] The conductive powder may be a powder having a nanometer or micrometer particle size, for example, a conductive powder having a particle size of tens to hundreds of nanometers or a conductive powder having a particle size of several micrometers to tens of micrometers. In addition, as the conductive powder, two or more conductive powders having different particle sizes may be mixed and used.
[0047] The average particle size of the conductive powder (D 50 ) can be 0.1 μm to 10 μm (for example, 0.5 μm to 5 μm), and within the above range, although the contact resistance and the series resistance may be reduced, it is not limited to this. The average particle size (D) can be measured by using the 1064LD model made by CILAS after ultrasonic dispersion of the conductive powder in isopropyl alcohol (IPA) for 3 minutes at 25°C. 50 ).
[0048] Although the amount of the conductive powder is not particularly limited, the conductive powder may be included in an amount of 60 to 95 weight percent (e.g., 70 to 90 weight percent) in the total weight of the composition for forming the solar cell electrode. In the above range, the conversion efficiency of the solar cell is high and gelatinization can be smoothly achieved.
[0049] Glass Frit
[0050] The glass frit is used to etch the anti-reflection film in the firing process of the composition for forming the solar cell electrode, and to melt the conductive powder to form crystalline particles of the conductive powder in the emitter region. In addition, the glass frit improves the bonding strength between the conductive powder and the wafer, and softens during sintering, thereby causing the effect of further reducing the firing temperature.
[0051] The glass frit can be calculated by the following formula 1, and α is 0.9 or more (for example, 0.9 to 5, another example is 1.2 to 5, and another example is 1.2 to 4). In this case, the power reduction of the battery caused by acid is reduced, so that long-term stability can be excellent.
[0052] <Formula 1>
[0053]
[0054] In Formula 1, C i is the content of the acidic compounds constituting the glass frit (unit: molar percentage), A i is the acidity of each acidic compound constituting the glass frit, n is the number of acidic compounds constituting the glass frit, C j is the content of each alkaline compound constituting the glass frit (unit: mole percentage), A j is the acidity of each basic compound constituting the glass frit, and m is the number of types of basic compounds constituting the glass frit.
[0055] Here, "acidity" may mean the acidity of binary oxides based on thermochemical data of Smith, DW An Acidity Scale for Binary Oxides. J. Chem. Educ. 1987, 64 (6), 480-481.
[0056] “Acidic compounds” may include acidic oxides, oxides that react with bases to generate bases (e.g., non-metals, etc.), and compounds that are decomposed into acidic oxides when melted; “basic compounds” may include basic oxides, oxides that react with acids to generate bases (e.g., alkali metals, alkaline earth metals, etc.), and compounds that are decomposed into basic oxides when melted; acidic oxides and basic oxides do not include amphoteric compounds.
[0057] The acidity of an acidic compound may be the same as that of an acidic oxide, which may mean an oxide having an acidity greater than zero, and the acidity of a basic compound may be the same as that of a basic oxide, which may mean an oxide having an acidity less than zero.
[0058] However, in the present invention, lead oxide and bismuth oxide are regarded as amphoteric compounds regardless of acidity, and are therefore excluded from the calculation considerations of Formula 1.
[0059] According to an example, the glass frit may contain 40 mol % to 60 mol % of the acidic compound, in which case, the stability to acid may be improved. For example, the glass frit may contain 45 mol % to 60 mol % of the acidic compound, and in another example, may contain 45 mol % to 55 mol % of the acidic compound, but is not limited thereto.
[0060] According to an example, the glass frit may contain 1 mol % to 25 mol % of the alkaline compound, in which case, it may have the effect of increasing the contact and electrode interface reaction on the silicon wafer. For example, the glass frit may contain 1 mol % to 20 mol % of the alkaline compound, and in another example, may contain 5 mol % to 15 mol % of the alkaline compound, but is not limited thereto.
[0061] According to one example, the glass frit may contain the acidic compound and the alkaline compound in a total amount of 45 mol% to 75 mol%, in which case, excellent effects in terms of electrical properties and long-term stability may be achieved. For example, the glass frit may contain the acidic compound and the alkaline compound in a total amount of 45 mol% to 70 mol%, and in another example, the glass frit may contain the acidic compound and the alkaline compound in a total amount of 50 mol% to 70 mol%, but is not limited thereto.
[0062] According to an example, the glass frit may include one or more elements selected from the group consisting of lead (Pb), bismuth (Bi), tellurium (Te), lithium (Li), sodium (Na), phosphorus (P), silicon (Si), zinc (Zn), germanium (Ge), calcium (Ca), gallium (Ga), silver (Ag), iron (Fe), tungsten (W), magnesium (Mg), molybdenum (Mo), niobium (Nb), strontium (Sr), titanium (Ti), tin (Sn), indium (In), vanadium (V), barium (Ba), nickel (Ni), copper (Cu), potassium (K), selenium (Se), arsenic (As), cobalt (Co), zirconium (Zr), manganese (Mn), aluminum (Al), thallium (Tl), tantalum (Ta), cesium (Cs), cerium (Ce), and boron (B). The properties and acidity of compounds containing these elements may refer to the following Table 1.
[0063]
Table 1
[0064]
[0065]
[0066] According to an example, the glass frit may include lead (Pb), bismuth (Bi) and tellurium (Te). In this case, it may help to improve the surface contact and electrical characteristics of the electrode. For example, the glass frit may include lead (Pb) and bismuth (Bi) in a total amount of 20 mol% to 45 mol% (e.g., 25 mol% to 40 mol%), and tellurium (Te) in a total amount of 10 mol% to 60 mol% (e.g., 20 mol% to 55 mol%), but is not limited thereto. At this time, the molar ratio of lead (Pb) to bismuth (Bi) may be 1:2 to 1:15 (e.g., 1:3 to 1:10), but is not limited thereto.
[0067] According to an example, the glass frit may contain lithium (Li). In this case, it may be helpful to form silver (Ag) crystals and improve the open circuit voltage (Voc). For example, the glass frit may contain lithium (Li) at 0.1 mol % to 25 mol % (e.g., 1 mol % to 20 mol %), but is not limited thereto.
[0068] According to an example, the glass frit may contain sodium (Na). In this case, it may facilitate the contact with the electrode and the formation of silver (Ag) crystals that affect the resistance. For example, the glass frit may contain sodium (Na) at 0.1 mol % to 10 mol %, but is not limited thereto.
[0069] According to an example, the glass frit may contain magnesium (Mg). In this case, it may help to increase the contact reaction of the electrode and reduce the contact resistance. For example, the glass frit may contain magnesium (Mg) at 0.1 mol % to 25 mol % (e.g., 0.1 mol % to 15 mol %), but is not limited thereto.
[0070] According to an example, the glass frit may contain zinc (Zn). In this case, it may help to increase the contact reaction of the electrode and the formation of silver (Ag) crystals. For example, the glass frit may contain zinc (Zn) at 0.1 mol % to 25 mol % (e.g., 0.1 mol % to 15 mol %), but is not limited thereto.
[0071] According to an example, the glass frit may contain tungsten (W). In this case, the glass frit can be easily manufactured and can help improve Voc. For example, the glass frit may contain tungsten (W) at 0.1 mol % to 30 mol % (e.g., 1 mol % to 20 mol %), but is not limited thereto.
[0072] According to an example, the glass frit may contain silicon (Si). In this case, the glass frit can be easily manufactured and can help improve Voc. For example, the glass frit may contain silicon (Si) at 0.1 mol % to 30 mol % (e.g., 1 mol % to 25 mol %), but is not limited thereto.
[0073] According to an example, the glass frit may contain boron (B). In this case, the glass frit can be easily manufactured and can help improve Voc. For example, the glass frit may contain boron (B) at 0.1 mol % to 10 mol % (e.g., 0.5 mol % to 5 mol %), but is not limited thereto.
[0074] The shape and size of the glass frit are not particularly limited. For example, the shape of the glass frit can be spherical or amorphous, and the average particle size (D 50 ) can be 0.1 μm to 10 μm. The average particle size (D) can be measured by ultrasonically dispersing the glass material in isopropyl alcohol (IPA) at 25°C for 3 minutes and then using a 1064LD model made by CILAS. 50 ).
[0075] Glass frit can be prepared from the elements and / or element compounds using a common method. For example, after mixing the elements and / or element compounds using a ball mill or a planetary mill, the mixed composition is melted at 800° C. to 1300° C., quenched at 25° C., and then the obtained product is pulverized by a disk mill, a planetary mill, etc., thereby obtaining glass frit.
[0076] The amount of glass frit used is not particularly limited, for example, in the total weight of the composition for forming the solar cell electrode, 0.1 weight percent to 20 weight percent (for example, 0.1 weight percent to 10 weight percent) of glass frit may be included. Within the range, pn junction stability can be ensured in a variety of sheet resistances, and resistance can be minimized, which can ultimately improve the efficiency of the solar cell.
[0077] Organic carrier
[0078] The organic vehicle can impart suitable printing viscosity and rheological properties to the composition through mechanical mixing with the inorganic components of the composition for forming a solar cell electrode.
[0079] The organic vehicle may be generally an organic vehicle used in a composition for forming a solar cell electrode, and may include a binder resin, a solvent, and the like.
[0080] Acrylic or cellulose resins can be used as the base resin. For example, ethyl cellulose can be used as the base resin. As another example, hydroxyethyl cellulose, nitrocellulose, a mixture of ethyl cellulose and phenolic resin, alkyd resin, phenolic resin, acrylic resin, xylene resin, polybutylene resin, polyester resin, urea resin, melamine resin, vinyl acetate resin, rosin, polymethacrylate of ethanol, etc. can be used as the base resin alone or in combination.
[0081] For example, hexane, toluene, ethyl cellosolve, cyclohexanone, butyl cellosolve, butyl carbitol (diethylene glycol monobutyl ether), dibutyl carbitol (diethylene glycol dibutyl ether), butyl carbitol acetate (diethylene glycol) ethylene glycol monobutyl ether acetate), propylene glycol monomethyl ether, hexylene glycol, pinene alcohol, methyl ethyl ketone, benzyl alcohol, γ-butyrolactone, ethyl lactate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (for example, Texanol), etc. can be used as solvents alone or in combination.
[0082] Although the amount of the organic vehicle used is not particularly limited, for example, 1 to 30 weight percent (e.g., 3 to 20 weight percent) of the organic vehicle may be included in the total weight of the composition for forming a solar cell electrode. Within the range, sufficient bonding strength and excellent printability may be ensured.
[0083] additive
[0084] In addition to the above ingredients, the composition for forming the solar cell electrode may further include a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoamer, a pigment, a UV stabilizer, an antioxidant, a coupling agent, or two or more of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoamer, a pigment, a UV stabilizer, an antioxidant, and a coupling agent as needed to improve flow characteristics, process characteristics, and stability. These may be included in an amount of 0.1 to 5 weight percent in the total weight of the composition for forming the solar cell electrode, and their content may be changed as needed.
[0085] Solar cell electrode and solar cell including the same
[0086] According to another embodiment, a solar cell electrode formed using the composition for forming a solar cell electrode and a solar cell including the same are provided. Figure 1 The figure briefly shows the structure of a solar cell (100) according to an example of the present invention.
[0087] Reference Figure 1, a composition for forming a solar cell electrode can be printed on a wafer or substrate (10) including a p-layer (or n-layer) (11) and an n-layer (or p-layer) (12) as an emitter and fired to form a back electrode (21) and a front electrode (23). For example, after printing and applying the composition for forming a solar cell electrode on the back surface of the wafer, the composition can be dried for 10 seconds to 60 seconds at 200°C to 400°C to perform a preliminary preparation step for the back electrode. In addition, after printing the composition for forming a solar cell electrode on the front surface of the wafer, the composition can be dried to perform a preliminary preparation step for the front electrode. Thereafter, a firing process of firing for 30 seconds to 210 seconds at 400°C to 950°C can be performed to form the front electrode and the back electrode.
[0088] Hereinafter, an embodiment is given to further describe in detail a composition for forming a solar cell electrode according to an example of the present invention. However, it should be explained that this is only presented as a preferred example of the present invention, and the present invention cannot be limited thereby in any sense.
[0089] Example
[0090] Example 1
[0091] At 60°C, 2 parts by weight of ethyl cellulose (STD4, Dow Chemical) as a base resin was fully dissolved in 6.5 parts by weight of terpineol (Nippon Terpine) as a solvent, and then 90 parts by weight of spherical silver powder (4-8F, Dowa) with an average particle size of 2.0 μm and 1.5 parts by weight of glass frit A shown in Table 2 below with an average particle size of 1.0 μm were added and uniformly mixed, and then mixed and dispersed using a 3-roll kneader to prepare a composition for forming a solar cell electrode.
[0092] Examples 2 to 4 and Comparative Examples 1 to 4
[0093] A composition for forming a solar cell electrode was prepared by the same method as in Example 1 except that glass frits B to H in Table 1 below were used instead of glass frit A.
[0094]
Table 2
[0095] (Unit: mole percent)
[0096]
[0097] Evaluation example
[0098] After using a 380 mesh to first dope a 5μm thick doping paste containing P as a Group 5 element (Honeywell) on one side of a p-type semiconductor substrate to form an electrode pattern, it is heat treated at 300°C for 5 minutes to dry. At 50°C, the substrate is injected with POCl3 gas in a diffusion furnace to perform a second doping to produce a selective emitter layer. After the second doping is completed, HF is used to remove PSG (phosphersilicate glass) on the surface of the substrate, and SiN is coated on the surface using PECVD to form an anti-reflection film. Thereafter, aluminum paste is printed on the rear surface of the substrate, and dried at 300°C for 30 seconds to form a back electrode, and the prepared composition for forming a solar cell electrode is arranged and printed on the electrode pattern using a baccini printer, and then dried at 300°C for 30 seconds to form a front electrode. The cells formed by the process were fired using a belt furnace at between 640°C and 700°C for 45 seconds to make solar cells.
[0099] For the solar cell produced in this manner, the conversion efficiency reduction rate (unit: %) was measured using the acetic acid test (AAT) for evaluating acid stability, and the results are presented in the following Table 3. The evaluation method is as follows:
[0100] (1) Before AAT is performed, the efficiency of the fired cells is measured and the cells are placed in a wafer storage rack for preparation. At this time, it is necessary to ensure a sufficient interval between the cells and prepare a plurality of cells for one sample.
[0101] (2) Potassium chloride and deionized water were placed in a 20 L container. The potassium chloride was crushed so that the size of the lumps did not exceed 1 cm, and then a 99% acetic acid solution was measured and added.
[0102] (3) A fan is provided on one side of the 20L container so that the acetic acid vapor can be circulated evenly in the container during the measurement process.
[0103] (4) Place the holder with the measurement battery in the prepared container, seal it, and place it in an oven set to 80°C for 6 hours. At this time, check whether the fan is working properly.
[0104] (5) After the measurement, the battery was thoroughly washed with deionized water and then dried.
[0105] (6) After measuring the efficiency of the dried battery, the efficiency decrease values before and after the measurement are calculated.
[0106]
Table 3
[0107] Efficiency decrease % Example 1 1.2 Example 2 1.1 Example 3 1.0 Example 4 2.0 Comparative Example 1 13.0 Comparative Example 2 9.0 Comparative Example 3 7.0 Comparative Example 4 11.0
[0108] It can be seen from Table 3 that the solar cells formed by using the compositions for forming solar cell electrodes of Examples 1 to 4 of the present invention containing glass material have a smaller reduction in conversion efficiency before and after acid treatment (AAT) than Comparative Examples 1 to Comparative Examples 4 that do not use such compositions, and the results show excellent long-term stability.
[0109] The present invention has been observed above with multiple embodiments as the center. As long as one is of ordinary skill in the technical field to which the present embodiment belongs, it can be understood that it can be embodied in a deformed form within the scope that does not deviate from the essential characteristics of the present invention. Therefore, the multiple embodiments disclosed should not be considered only from a limiting point of view, but should be considered from an illustrative point of view. The scope of the present invention is presented in the scope of the invention claims, rather than in the above description, and all differences within the same scope should be interpreted as being included in the present invention.
Claims
1. A method for improving the acid resistance of a solar cell, wherein the solar cell comprises an electrode, and acetic acid exists in the working environment of the electrode, characterized in that: The composition for forming the electrode comprises conductive powder, glass frit and an organic carrier. The glass frit is calculated by the following formula 1, and α is greater than 0.9: <Formula 1> In formula 1, C i is the content of the acidic compounds constituting the glass frit, expressed in mole percentage, A i is the acidity of each of the acidic compounds constituting the glass frit, n is the number of acidic compounds that make up the glass frit, C j is the content of each alkaline compound constituting the glass frit, expressed in mole percentage, A j is the acidity of each alkaline compound constituting the glass frit, m is the number of kinds of basic compounds constituting the glass frit.
2. The method according to claim 1, characterized in that: The glass frit includes an acidic compound at 40 mol % to 60 mol %.
3. The method according to claim 1, characterized in that The glass frit includes a basic compound at 1 mol % to 25 mol %.
4. The method according to claim 1, characterized in that The glass frit includes an acidic compound and a basic compound in a total amount of 45 mol % to 75 mol %.
5. The method according to claim 1, characterized in that: The glass frit is calculated by the formula 1, and α is 0.9 to 5.
6. The method according to claim 1, characterized in that The glass frit includes one or more elements selected from the group consisting of lead (Pb), bismuth (Bi), tellurium (Te), lithium (Li), sodium (Na), phosphorus (P), silicon (Si), zinc (Zn), germanium (Ge), calcium (Ca), gallium (Ga), silver (Ag), iron (Fe), tungsten (W), magnesium (Mg), molybdenum (Mo), niobium (Nb), strontium (Sr), titanium (Ti), tin (Sn), indium (In), vanadium (V), barium (Ba), nickel (Ni), copper (Cu), potassium (K), selenium (Se), arsenic (As), cobalt (Co), zirconium (Zr), manganese (Mn), aluminum (Al), thallium (Tl), tantalum (Ta), cesium (Cs), cerium (Ce), and boron (B).
7. The method according to claim 1, characterized in that The glass frit includes lead (Pb), bismuth (Bi) and tellurium (Te), The glass frit includes lead (Pb) and bismuth (Bi) in a total amount of 20 mol % to 45 mol %, and includes tellurium (Te) in a total amount of 10 mol % to 60 mol %.
8. The method according to claim 7, characterized in that The glass frit further includes one or more elements selected from the group consisting of lithium (Li), sodium (Na), magnesium (Mg), zinc (Zn), tungsten (W), silicon (Si), and boron (B).
9. The method according to claim 8, characterized in that The composition for forming the electrode: The lithium (Li) is contained in an amount of 0.1 mol % to 25 mol %, The sodium (Na) is contained in an amount of 0.1 mol % to 10 mol %, The magnesium (Mg) is contained in an amount of 0.1 mol % to 25 mol %, The zinc (Zn) is contained in an amount of 0.1 mol % to 25 mol %, The tungsten (W) is contained in an amount of 0.1 mol % to 30 mol %, The silicon (Si) is contained in an amount of 0.1 mol % to 30 mol %, The boron (B) is contained in an amount of 0.1 mol % to 10 mol %.
10. The method according to claim 1, characterized in that The composition for forming the electrode further comprises at least one of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoaming agent, a pigment, an ultraviolet stabilizer, an antioxidant and a coupling agent.
11. The method according to claim 1, characterized in that The composition for forming the electrode comprises: 60 to 95 weight percent of the conductive powder; 0.1 to 20 weight percent of the glass frit; and 1 weight percent to 30 weight percent of the organic carrier.
Citation Information
Patent Citations
Paste composition for preparing solar cell electrode, solar cell electrode and solar cell
CN106601335A